The more the merrier? Migration and convergence among European regions - Lorenz B. Fischer; Michael Pfaffermayr (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2015)
Using a spatial systems estimator to incorporate spatial interactions and endogeneity of income levels and migration, this paper finds a positive effect of migration on cohesion within the European Union on the NUTS 2 level. As migration can generally be observed from low to high income regions, growth rates of income per worker tend to decrease in regions experiencing net immigration, while lagging regions experience higher speeds of income convergence. As a result, migration increases sigma-convergence. Results show an increase of more than one third. Free movement of persons also proves to increase efficiency, displayed by higher average convergence speeds.
Keywords: R11; C31; O47; 330; Conditional spatial beta- and sigma-convergence; Migration; Spatial Solow model; European regions